Hubungan Pola Asuh Orang Tua dan Tingkat Ekonomi Keluarga Terhadap Prestasi Belajar Mahasiswa - Syahlan, Fatra; Nugraha, Derry (Journal of Education and Culture, 2023)
This study aims to determine the parenting style and family economic level on student achievement. The population in this study were students STKIP PGRI Sukabumi.The type of research used is descriptive quantitatif. Samples in the study were 100 respondents with data collection techniques in the form of a questionnaire (questionnaire). The data obtained were analyzed using validity and reliability tests. In addition, the data is used using hypothesis testing including multiple linear regression tests, t-tests, f-tests and coefficient of determination tests. The results showed that: 1) there is a significant influence between parenting style on student achievement. The results of the data obtained that the sig value for X1 to Y is 0,00 < 0,05 and calculated t value 3,932 > t table 1,984, 2) there is no significant influence between the economic level of the family on student achievement. The results of the data obtaine that the sig value for X2 to Y is 0,587 > 0,05 and calculated t value 0,545 < 1,984, 3) there is a significant influence between parenting style and family economic level on student achievement. The results the data obtained that the sig value for X1 and X2 simultaneously against Y of 0,000 < 0,05 and calculated F value 12,197 > 3,09. And can also be seen from the calculated of the coefficient of determination It is know that the value of r square is equal to 0,201 this means that the influence of variables X1 and X2 simultaneously to Y is 44,8%.